PSIKOEDUKASI KESADARAN KESEHATAN MENTAL: UPAYA PREVENTIF & PROMOTIF DI LINGKUNGAN SEKOLAH - Deasyanti; Ade Siti Mariyam; Dewinta Arianti; Kahfi Hizbullah (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2025)
Mental health awareness is a crucial element in creating a school environment that supports the well-being of school members. A psychoeducational program on mental health was implemented for teachers and educational staff at a junior high school in Jakarta. The program aimed to strengthen teachers and educational staffs with fundamental knowledge of mental health, enabling them to conduct early identification of potential psychological problems, reduce stigma, and encourage professional help-seeking behaviour. Post-test findings demonstrated a significant improvement in participants’ knowledge of basic mental health. Furthermore, through practical exercises, participants gain hands-on skills in providing initial support to others experiencing mental health issues. Strengthening collective mental health awareness is expected to foster a healthy, inclusive, and supportive school climate. Abstrak Kesadaran kesehatan mental merupakan aspek yang penting dalam mengembangkan lingkungan sekolah yang peduli terhadap kesejahteraan mental semua warga sekolah. Program psikoedukasi kesehatan mental diberikan kepada sejumlah guru dan tenaga kependidikan di salah satu SMP di Jakarta. Psikoedukasi ini bertujuan agar guru dan tenaga kependidikan memiliki pemahaman dasar tentang kesehatan mental sehingga mampu melakukan deteksi dini masalah mental, mengurangi stigma, serta dapat mendorong individu untuk mencari bantuan profesional. Hasil intervensi psikoedukasi terbukti dari peningkatan skor post-test tentang pengetahuan dasar kesehatan mental. Selain itu, melalui latihan praktis, peserta memiliki keterampilan dalam memberikan dukungan awal terhadap orang lain yang sedang mengalami masalah mental. Dengan peningkatan kesadaran kesehatan mental secara kolektif diharapkan dapat tercipta iklim sekolah yang sehat, inklusif, dan suportif.